2004
DOI: 10.1158/0008-5472.can-03-3424
|View full text |Cite
|
Sign up to set email alerts
|

Laminin-Induced Signaling in Tumor Cells

Abstract: The expression of the M r 67,000 laminin receptor, a nonintegrin laminin receptor, was found to be up-regulated in neoplastic cells and to directly correlate with invasion and metastatic potential. In the present study, we investigated the role of laminin receptor in mediating laminin effects and the involvement of the mitogen-activated protein kinases (MAPK) cascades and dual-specificity phosphatases in laminin signaling in human melanoma cells. Using stable transfection of A375SM melanoma cells, we establish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
133
0
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 172 publications
(139 citation statements)
references
References 55 publications
3
133
0
3
Order By: Relevance
“…The 67LR protein is a cellular receptor for cell adhesive protein laminin and a 37 kDa protein is the precursor of the receptor, although the exact manner by which it configures its mature form is not clear (4). Previous studies have shown that the cell sur- HL-60 cells similar to that of normal monocytic cells (1).…”
Section: Expression Of 67lrmentioning
confidence: 99%
“…The 67LR protein is a cellular receptor for cell adhesive protein laminin and a 37 kDa protein is the precursor of the receptor, although the exact manner by which it configures its mature form is not clear (4). Previous studies have shown that the cell sur- HL-60 cells similar to that of normal monocytic cells (1).…”
Section: Expression Of 67lrmentioning
confidence: 99%
“…During tumor invasion and metastasis, cancer cells are known to interact with laminin. For instance, a nonintegrin receptor known as M r 67-kDa laminin receptor, which can interact with ␣6-integrin, has been shown to induce laminin signaling in tumor cells through mitogen-activated protein kinases cascades (52,53). This 67-kDa laminin receptor has high affinity toward laminin through the binding site of peptide G (54).…”
Section: Laminin-333⅐␣6␤1-integrin Is a Putative Adhesion Protein Commentioning
confidence: 99%
“…In particular, human TSP1 shows the highest identity (22%) with the corresponding region of hNELL1. The laminin G domain serves in the interaction with integrins and a 67-kDa laminin receptor [26]. Mutational analyses of TSP1 and TSP2 have demonstrated that a Glu residue (Glu-90) between b-strands D and E is important for the interaction with integrin a6b1, which is conserved in the similar positions of hNELL1 [22] (Fig.…”
Section: Putative Nell1 Receptormentioning
confidence: 99%